Mengembangkan Hasil Belajar Matematika dengan Media Alat Peraga untuk Siswa Kelas III SDN 09 Kepahiang - Fitrah, Fitrah (Jurnal PGSD, 2020)
This study aims to develop Mathematical learning outcomes in the aspect of fractions with the help of Props Media for 3rd year students of SDN 09 Kepahiang Academic Year of 2019/2020. This research used a Classroom Action Research (CAR) design. Participants or subjects in this study amounted to 20 students, who were divided into 8 boys and 12 females. Data Collection techniques in this study including Test, Observation and Documentation. This research was carried out through two cycles. Data analysis techniques include: 1) Data Reduction; 2) Data Presentation, 3) Conclusion Withdrawal or Verification. From the research and the dicussion the result was found, such as: the average value generated by learning achievement for Mathematics subjects for 3rd year students that appeared in Cycle I amounted to 68.0, in Cycle II amounted to 77.5 so that there was a significant increase in the average value of the Cycle I research into Cycle II research. The percentage of mastery learning obtained in Cycle I is illustrated by a figure of 75.0% (15 students succeeded in completing their learning from a total of 20 students), and in Cycle II the percentage of mastery learning was 90.0% (18 students successfully completed their learning from total 20 student). With these results it can be said that there was a remarkable improvement in student learning completeness from Cycle I to Cycle II. The conclusion of this research is, with the help of Media Teaching Aids can improve and develop learning outcomes in mathematics for students of 3rd year SDN 09 Kepahiang Academic Year of 2019/2020.